Sintesis Nanohibrida Silika-urea Berbasis Abu Bagasse sebagai Pupuk Lepas Lambat Ramah Lingkungan - Siti Muslimah; Nazriati; Neena Zakia (Talenta Publisher (Universitas Sumatera Utara), 2025)
The urea–silica nanohybrid is an innovative slow-release fertilizer designed to enhance nitrogen use efficiency in agriculture. This study synthesized the nanohybrid using silica sourced from bagasse ash via the sol-gel method. Silica was extracted by reacting the ash with sodium hydroxide to form sodium silicate, which was then converted into silicic acid through ion exchange using a cation resin. Ammonium hydroxide was added to adjust the pH to 5, forming a gel at room temperature. The gel was aged for 18 hours to strengthen its structure, then freeze-dried to produce hydrophilic silica aerogel. To form the nanohybrid, 1 g of silica aerogel was mixed with urea at varying concentrations, stirred for 24 hours, filtered, and dried at 40 °C. Characterization using Fourier Transform Infrared Spectroscopy (FTIR) confirmed the presence of Si–O–Si and Si–OH groups, along with urea-specific bands (C=O and N–H), indicating successful integration of urea into the silica matrix.